Fangled Protocol for Black Hole Detection in Ad Hoc Networks (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Now a day, security in Mobile Ad hoc Network is very important issue. Due to dynamic topology and mobility of nodes, Mobile Ad hoc Networks are more vulnerable to security attacks than conventional wired and wireless network. Nodes of Mobile Ad hoc Network communicate directly without any central base station. That means in ad hoc network, infrastructure is not required for establishing communication. Therefore attacks in this are very frequent than other networks. In this research paper we are describing black hole attacks which are easy to launch in wireless ad hoc network. Black hole attack is referred to as a node dropping all packets and sending forged routing packets to route packets over itself. Ad hoc networks are vulnerable to different kinds of attacks such as: denial of services, impersonation, and eavesdropping.This paper discusses one of the security problems in ad hoc networks called the black hole problem. It occurs when a malicious node referred as black hole joins the network. The black hole conducts its malicious behaviour during the process of route discovery. For any received REQ, the black hole claims having a route and propagates a faked REP. The source node responds to these faked REPs and sends its data through the received routes. Once the data is received by the black hole, it is dropped instead of being sent to the desired destination.The proposed protocol is built on top of the original AODV. It extends the AODV to include the following functionalities: source node waits for a reliable route; each node has a table in which it adds the addresses of the reliable nodes; REP is overloaded with an extra field to indicate the reliability of the replying node.Â